UiTM Professorial Lecture : personalised therapy : the perspective of pharmaceutical technology / Wong Tin Wui - Wong, Tin Wui
The book is written in conjunction with professorial lecture 2022 to be held in Universiti Teknologi MARA, Malaysia. It aims to summarize my research progress in the arena of pharmaceutics and biopharmaceutics. Looking through the past research studies, my research focus first begins with particle design where physics and chemistry are topics of concern in the mechanistic elucidation of the development of a delivery system. Much efforts are devoted in oral drug delivery system design from the perspectives of innovative material/formulation sciences and processing technology dealing with small molecule drugs. In 2006, the research focus gears toward diabetes and oral insulin delivery. The study integrates physics, chemistry and biology elements in a single attempt, and macromolecular therapeutic is employed as the drug of interest for the first time. In 2008 and thereafter, I venture into skin and pulmonary drug delivery. Synthetic chemistry and microwave physics become the main lead in new science creation. Through extensive international and national collaborations, my team and myself are now heading in the direction of new particle designs involving fundamental understanding from the roots of molecular biology and molecular pharmaceutics.